Investments in the Brazilian space agency and the patenting process: A correlation analysis - Vitor Hugo da Silva Vaz; Jorge Maikel Alves Batista; Ana Eleonora Almeida Paix\~ao (Innovation & Management Review, 2019)
Purpose - This study aims to analyze the correlation between the investments in the Brazilian Space Agency (BSA) and the patenting process. Design/methodology/approach The methodology used was a statistical analysis through correlation and linear regression between the secondary data of investments made by the federal government, retrieved from the Transparency Portal, in the BSA and the patenting process, taking into consideration the number of invention, utility model and certificate of addition of invention. Findings After a brief presentation of the emergence of innovation and patent applications with the investments of governments in space agencies, this study presents the analysis of information in different times of investment that showed positive correlation between the two variables adopted. Originality/value One can point to the value of this study as strategic investments in space agencies to boost the filing of patents in a nation in the most diverse areas.
Keywords: 650; Innovation; Patent; Correlation; Space agency